Sirtuin 1 expression in elderly patients with type 2 diabetes mellitus - Mohamed M. M. Hassaan; Imam M. Esmayel; Mayada M. Mousa; Samia Hussein; Ahmed K. Y. Alkolaly; Batoul A. Hegazy; Rodalia M. Makhlouf (Egyptian Journal of Medical Human Genetics)
Abstract Background The sirtuin (SIRT) family has a crucial role in aging biology. SIRT1 is a NAD+-dependent deacetylase. SIRT2 is an NAD-dependent deacetylase that mediates deacetylation of alpha-tubulin. SIRT3 is a mitochondrial enzyme that regulates mitochondrial functions, including ATP synthesis, reactive oxygen species production, fatty acid oxidation, ketone metabolism, and cellular death. SIRT4 is an ADP-ribosyltransferase that downregulates glutamate dehydrogenase in β cells, with a subsequent reduction in insulin secretion. SIRT5 regulates post-translational modifications. SIRT6 is a mono-ADP-ribosyl transferase. SIRT7 is present in the nucleoli and controls RNA polymerase I. The SIRT1 gene is present on chromosome 10 at the 10q21.3 locus. Methods This study included 2 groups. Group 1 included 35 elderly patients with type 2 diabetes mellitus (T2DM). Group 2 included 35 elderly non-diabetic subjects. Laboratory investigations included complete blood picture and kidney and liver function tests. Lipid profile, fasting blood sugar (FBS), two-hour postprandial blood sugar (2-h-PPS), and hemoglobin A1c (HbA1c) were measured. SIRT1 protein and mRNA expressions were measured by enzyme-linked immunosorbent assay (ELISA) and real-time polymerase chain reaction (RT-PCR), respectively. Results No significant differences were detected between the two groups concerning hemoglobin (Hb) level, total leukocytic count, or platelet count (P = 0.064, 0.251, and 0.333, respectively). However, FBS, 2-h-PPS, and HbA1c were significantly higher in cases compared to controls (P < 0.001 for each). Additionally, total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C) were significantly higher in cases compared to controls (P < 0.001, 0.001, and 0.005, respectively). However, there was no significant difference in high-density lipoprotein cholesterol (HDL-C) (P = 0.314). SIRT1 mRNA and protein expressions were significantly higher in cases compared to controls (P  < 0.001, for both). SIRT1 had significant negative correlations with body mass index (BMI) (r = − 0.316, P = 0.006), duration of DM (r = − 0.308, P = 0.009), FBS (r = − 0.581, P < 0.001), 2-h-PPS (r = − 0.676, P < 0.001), HbA1c (r = − 0.648, P < 0.001), TC (r = − 0.232, P = 0.029), and LDL-C (r = − 0.263, P = 0.013). Conclusion SIRT1 mRNA and protein expressions were significantly upregulated in T2DM. SIRT1 expression had significant negative correlations with BMI, duration of DM, FBS, 2-h-PPS, HbA1c, TC, and LDL-C. BMI and HbA1c are determinants of SIRT1 expression in elderly patients with T2DM, as confirmed by regression analysis.